Wokół kategorii metaxú. Doświadczanie i wytwarzanie międzyludzkiego pogranicza za pomocą języka - Korwin-Piotrowska, Dorota (Tematy i Konteksty, 2019)
The subject of the paper consists in the reflections dedicated to the creation of the inter-human “borderland”. The metaxú category (Greek: μεταξύ, in-between) serves this purpose. Derived from antiquity, it was interpreted by Simone Weil in her book La Pésanteur et la Grâce (Gravity and Grace). The study develops Weil’s concept, and at the same time it expands it towards linguistics. A list of five notions is proposed. They present different aspects of metaxú, such as relationality, borderlandness, pragmatism, ambivalence, and transversality, which point to the anthropological and social role of the “in-between”. These notions are discussed in the paper at length, and then referred to the linguistic communication, which is treated exactly as a metaxú sphere.